2021
DOI: 10.3389/fpsyg.2021.600348
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Mathematics Academic Burden for Primary School Students Based on PISA Data Analysis

Abstract: To explore the impact of academic burden on the physical and mental health of primary school students, combined with the results of the Programme for International Student Assessment (PISA) report in 2018, the relationship among the development of mathematical literacy, mathematics academic burden, and the physical and mental health of primary school students is studied. First, the relationship between mathematical literacy and mathematics anxiety is analyzed, and related influencing factors and measurement me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…It is noteworthy that the prevalence of depression (9.9% vs. 9.4%) and anxiety (7.4% vs. 7.1%) slightly decreased after the policy was implemented. These findings indicated that the "Double Reduction" Policy might relieve adolescents' mental health, echoing the literature that academic burden negatively impacts on mental health [9,25]. We acknowledge that this decreasing trend is small.…”
Section: Discussionsupporting
confidence: 66%
“…It is noteworthy that the prevalence of depression (9.9% vs. 9.4%) and anxiety (7.4% vs. 7.1%) slightly decreased after the policy was implemented. These findings indicated that the "Double Reduction" Policy might relieve adolescents' mental health, echoing the literature that academic burden negatively impacts on mental health [9,25]. We acknowledge that this decreasing trend is small.…”
Section: Discussionsupporting
confidence: 66%
“…Surprisingly, ATRs of the lumbar part appeared to be larger in Shanghai, especially in female students. It is widely accepted that the study burden and pressure in Shanghai is greater than in other cities in China, and female adolescents are more likely to be sedentary rather than physically active ( 46 , 47 ). Studies have provided evidence that there was a positive relationship between long sedentary time and scoliosis, and negative relationship between enough physical activity time and scoliosis ( 48 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The implication of this research is to make an initial contribution to developing an authentic math literacy instrument by referring to the math literacy ability and the HOTS level of primary students. With the implementation of math literacy in learning activities, it is hoped that later, students will be able to understand, identify, apply and develop the role of mathematics in everyday life (Ketonen & Hotulainen, 2019;Wang, 2021). However, this study was limited to the number of participants taken from several schools in one area.…”
Section: Correct Answermentioning
confidence: 99%
“…In this case, primary students need a good conceptual understanding, such as analyzing, reasoning, and thinking when solving problems (Güner & Erbay, 2021;Umbara & Suryadi, 2019). In supporting students to master these abilities, it is necessary to integrate literacy activities into the mathematics learning process (Sumirattana et al, 2017;Wang, 2021). The success of literacy in mathematics learning can impact students' mathematical performance at the primary school level and the Bagus Ali Rachman / Primary Students' Math Literacy in terms of Higher Order Thinking Skill next level (Amir et al, 2019;Zainiyah & Marsigit, 2019).…”
Section: Introductionmentioning
confidence: 99%